1996
DOI: 10.1146/annurev.genet.30.1.405
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Dependent Protein Degradation

Abstract: A growing number of cellular regulatory mechanisms are being linked to protein modification by the polypeptide ubiquitin. These include key transitions in the cell cycle, class I antigen processing, signal transduction pathways, and receptor-mediated endocytosis. In most, but not all, of these examples, ubiquitination of a protein leads to its degradation by the 26S proteasome. Following attachment of ubiquitin to a substrate and binding of the ubiquitinated protein to the proteasome, the bound substrate must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
1,296
0
12

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,573 publications
(1,337 citation statements)
references
References 116 publications
18
1,296
0
12
Order By: Relevance
“…These include: its co-receptor Vps27 (Bilodeau et al, 2002); the E3 ubiquitin ligase Rsp5 and two of its regulatory partners, Rup1 and Bul1 (Belgareh-Touze et al, 2008;Kee et al, 2005); de-ubiquitinating peptidases, also referred to as DUbs [Upb2 and Ubp7 (Hochstrasser, 1996) (Ozkaynak et al, 1987)]. While a number of physical interactions link Rts3 to PP2A-related proteins (described above), genetic interactions also connect RTS3 to ubiquitin-dependent protein sorting.…”
Section: The Caffeine Suppressor Gene Interaction Networkmentioning
confidence: 99%
“…These include: its co-receptor Vps27 (Bilodeau et al, 2002); the E3 ubiquitin ligase Rsp5 and two of its regulatory partners, Rup1 and Bul1 (Belgareh-Touze et al, 2008;Kee et al, 2005); de-ubiquitinating peptidases, also referred to as DUbs [Upb2 and Ubp7 (Hochstrasser, 1996) (Ozkaynak et al, 1987)]. While a number of physical interactions link Rts3 to PP2A-related proteins (described above), genetic interactions also connect RTS3 to ubiquitin-dependent protein sorting.…”
Section: The Caffeine Suppressor Gene Interaction Networkmentioning
confidence: 99%
“…Smurf1 is a member of the Hect domain family of E3 ubiquitin ligases. Hect domain proteins represent a major subclass of E3 ligases and contain a conserved cysteine, located at the carboxyl terminal of the Hect domain, which is capable of forming a thioester bond with ubiquitin (Hochetrasser, 1996;Zhu et al, 1999). Mutation of this conserved cysteine residue to an alanine (C710A) abolished the ubiquitination and degradation activity of Smurf1 (Zhu et al, 1999).…”
Section: Ubiquitin-proteasome Degradation Of Bmp Signaling Proteinsmentioning
confidence: 99%
“…A second feature unique to the separate MOCS1A isoform produced by the bicistronic splice type is the invariant Gly-Gly dipeptide at its C-terminus (Figs+ 1, 2C)+ This distinctive feature may be significant, as a Gly-Gly dipeptide confers potent biological activity to the C-termini of other polypeptides, such as ubiquitin and ubiquitin-like proteins (Hochstrasser, 1996;Haas & Siepmann, 1997;Gray et al+, 1999)+ Any functional attributes specific to MOCS1A will only be revealed by future in vivo and in vitro analyses+ Nevertheless, it is evident that each MOCS1 splice form may encode proteins with distinct properties that would justify sustaining this gene structure and bimodal splice pattern over 700 million years+ Furthermore, the ratio of transcripts producing fused or separate polypeptides could differ during development or with environmental/dietary stimuli (Unkles et al+, 1997), consistent with our initial mouse studies suggesting tissue specificity+…”
Section: Models From Phylogenetic Comparisonsmentioning
confidence: 99%